INTEGRATING LOCAL KNOWLEDGE AND MODERN PRACTICES FOR SUSTAINABLE DURIAN CULTIVATION IN PADAWAN, SARAWAK - Daniel Ugih, Echoh; Juliana, Anas; Nur Auni, Ugong (2025)
This research, conducted in Padawan, Sarawak, explores sustainable durian cultivation by examining the integration of traditional knowledge and modern agricultural methods. Using a qualitative approach involving interviews with local farmers and agricultural officers, the study found that traditional knowledge is not widely applied to common durian varieties, with farmers employing a relatively simple cultivation approach. However, for hybrid varieties introduced by the agricultural office, farmers actively combine traditional knowledge with modern techniques and official guidance. This finding highlights the potential for integrating diverse knowledge systems when new methods are introduced. The research emphasizes the importance of valuing both traditional knowledge and scientific advancements in developing sustainable and productive durian farming systems that ensure the region's long-term viability